The complete book of running - Fixx, James F. (New York : Random House, 1977)
Concentrating on the psychological aspects of the sport as well as the physical ones, the author discusses running at all ages, what to eat and wear, running after a heart attack, preparing for and running a race, and much more.
Includes index
Bibliography: p. [290]-306
Keywords: Running; Jogging; Sports -- Psychological aspects; Running; Jogging; Sports -- Psychological aspects